Negotiating Salafism: Local Muslim Identity and Religious Adaptation in Banten - Rusyadi, Refki; Degaf, Agwin; Aziz, Muhammad Sulthon; Sirad, Mochamad Chobir (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
The expansion of Salafism has generated enduring tensions within the syncretic Islamic identity of Banten, where local traditions are deeply embedded in religious belief and practice. This study examines how Bantenese Muslims negotiate encounters between transnational Salafi doctrines and inherited forms of religiosity. Based on qualitative fieldwork, it finds that younger, urban Muslims are more exposed to Salafi interpretations through education and social networks, while rural communities largely preserve established traditions. These uneven encounters produce a fragmented yet adaptive religious landscape. Drawing on Berger and Luckmann’s theory of the social construction of reality, the article explains how processes of externalization, objectivation, and internalization shape patterns of religious negotiation. It advances the concept of selective adaptation to show how global Islamic movements intersect with, rather than replace, local religious identities. The findings demonstrate that Bantenese Muslims selectively adopt, reinterpret, or contest Salafi teachings, underscoring that religious change is context-dependent and shaped by resilient local traditions.